The HES-code and the data protection during COVID-19 pandemic in Turkey - Cangil, Sabah Mine (Bioethica, 2021)
Mobile applications are a beneficial tool to fight the coronavirus. With the mobile tracing applications, it became easier to cut the chain of transmission of the virus and reduce the number of daily cases. Many countries developed their applications and made them available to their citizens. While using these applications, it is necessary to protect the fundamental rights and freedoms of the individual. This frequent processing of individuals' health data has created legal problems regarding the protection of personal data. The purpose of this paper is to present a study on the Turkish Covid-19 tracing application “Hayat Eve Sığar-HES” and the legal issues behind the application.